Efficacy and Safety of Various Intravenous Thrombolytics for Acute Ischemic Stroke (AIS) at Various Dosages: A Systematic Review and Network Meta-Analysis - Yibin Hu; Shengxian Wu; Haixuan Zhang; Kangfeng Wang; Lijuan Zhang; Yizheng Ma; He Li (Neurology and Therapy)
Abstract Background Currently, there is limited evidence on the efficacy and safety of various thrombolytic drugs at different dosages for the treatment of acute ischemic stroke (AIS). From current randomized clinical trials, the optimal type and dosage of thrombolytics for patients with AIS are unclear. Methods This systematic review was registered in PROSPERO (CRD42024563757). We searched four databases using a combination of keywords that contained various intravenous thrombolytics, as well as acute ischemic stroke. Only data from participants with AIS treated with various intravenous thrombolytics within the 4.5-h time window were included. Among initially identified studies, 16 met the selection criteria. Network meta-analysis was conducted for efficacy (90 day modified Rankin scale score) and safety (intracranial hemorrhage events, mortality at 90 days) using Stata 17.0 software, with a fixed-effects model. Cochrane risk of bias tool assessed all risk of bias domains, and the CINeMA Evidence Assessment Tool evaluated the level of evidence for each outcome. Results A total of 9056 studies were retrieved through the literature search, and 12,792 patients screened from 16 randomized controlled trials were included in the network meta-analysis. The risk of bias in the included studies ranged from moderate to low. The network meta-analysis results indicated that reteplase at 18 + 18 mg ranked highest in efficacy, though its safety was lower compared to 0.25 mg/kg tenecteplase and alteplase. The dose of 0.25 mg/kg tenecteplase emerged as the optimal dose, demonstrating both superior efficacy and a lower risk of bleeding compared to alteplase, making it a potential alternative to alteplase. The dose of 50 mg prourokinase was associated with the highest risk of symptomatic intracranial hemorrhage and was inferior to reteplase in terms of both efficacy and safety. The CINeMA Evidence Assessment Tool identified one outcome with a high level of evidence, several with moderate levels, and the remainder with low levels. Conclusions Reteplase at 18 + 18 mg may be more suitable for patients with lower incidence of adverse events evaluated by physicians. Compared to 0.9 mg/kg alteplase, 0.25 mg/kg tenecteplase is more effective, with the lowest risk of intracranial hemorrhage. However, as tenecteplase’s dosages increase (0.32 mg/kg and 0.4 mg/kg), its efficacy in improving neurological deficits decreases, while the risk of intracranial hemorrhage and death (especially at 0.4 mg/kg) increases. Clinicians are supposed to carefully assess the needs of patients with AIS and the risks then choose decent thrombolytics.